Aprovechamiento de residuos de yuca (Manihot esculenta Crantz) como aporte nutricional del chame (Dormitator latifrons) con fines de economía circular - Lynch Salvatierra, Ilma Jessenia (2021)
This research was carried out in the "San Pablo de Tarugo" community, belonging to Chone canton, Manabí province, with the objective of taking advantage of cassava waste (Manihot esculenta Crantz) as a nutritional contribution of chame (Dormitator latifrons) for economic purposes circular. For this, the socio-economic activity in the community was characterized, where it was determined that cassava rallanderías are fundamental to the economy of the sector, having a production of 200 to 600 kg per week, being the most used variety INIAP Portoviejo 651. A silage process of the residues from the production of cassava starch was carried out, from which the food used in the feeding of the chames was obtained. A completely randomized design (DCA) was applied with 95% significance. The food proportions were supplied as follows: T1 = 150 g, T2 = 100 g, T3 = 75 g and the control fed with water hyacinth (Eichhornia crassipes), with 3 repetitions respectively, evaluating 3 fundamental variables in the chame (weight, total length and width). The treatment that presented the best results in the experiment was T3, obtaining averages of weight 59,89 g, total length 16,88 cm and width 9,15 cm, while the treatment that presented the lowest yield was T1, with 45 g weight, 12,19 cm in length and 7,36 cm in width. Finally, a unit price analysis was applied to estimate the production cost of cassava waste silage, resulting in $ 0,85 per kg.